Ministerial Decree No. 204/2013 on Amending Some Provisions of the Executive Regulations of the Customs Law = قرار وزاري رقم 204 لسنة 2013 بتعديل بعض أحكام اللائحة التنفيذية لقانون الجمارك / Minister Prime - Egypt. Minister Prime (2025)
Ministry of Finance Decree No. 204 of the year 2013 on amending some provisions of the executive regulations of the customs law وزارة المالية قرار رقم 204 لسنة 2013 بتعديل بعض أحكام اللائحة التنفيذية لقانون الجمارك